Syllabus Design for Writing Course: EFL Learners’ Needs - Abbas, M. Fadhly Farhy; Syarif, Hermawati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Analyzing English as Foreign Language (EFL) learners’ needs in writing courses is an important thing that should be done by teachers. This is done in order to meet what EFL learners needs for writing course, and what should be planned and written in the syllabus. The purpose of this research is to analyze EFL learners’ needs for writing course especially in terms of learning materials, learning strategies, learning supports, and mastery of writing aspects. The design of this research was descriptive research. 50 EFL learners in Universitas Lancang Kuning were involved in this study as respondents of this research. To collect the data, a questionnaire was used with 20 statements available. The data from the questionnaire was analyzed descriptively by giving deep explanation towards the data. The result showed that most EFL learners were chosen response “agree” from the questionnaire. It means that the EFL learners very need good and acceptable learning materials, learning strategies, learning supports, and good competence in terms of writing aspects. In conclusion, the EFL learners’ needs for writing course are varied, but in general, the EFL learners expect good learning environment for writing course such as utilizing appropriate technology, attractive teaching media, and acceptable learning materials.